1991
DOI: 10.1159/000174867
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Late Potentials in the Assessment of Mitoxantrone Cardiotoxicity

Abstract: Sixteen female patients underwent signal-averaged electrocardiography and radionuclide angiography for the assessment of the resting left ventricular ejection fraction in the course of chemotherapy with mitoxantrone (MTX) for advanced breast cancer. Nine patients had received prior cardiotoxic treatments. Our findings indicate that patients treated with MTX may develop late potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…MIT causes cardiotoxicity by a different mechanism from those of doxorubicin and epirubicin, which are probably mediated by oxygen-free radicals [3]. One report indicated that patients treated with MIT may develop late potentials [5]. Another revealed that MIT induced a gradual, competitive P-adrenergic blocking effect against the positive chronotropic action of isoproterenol [6].…”
Section: Bradycardia Due To Mitoxantrone Exacerbated By Previous Anthmentioning
confidence: 99%
“…MIT causes cardiotoxicity by a different mechanism from those of doxorubicin and epirubicin, which are probably mediated by oxygen-free radicals [3]. One report indicated that patients treated with MIT may develop late potentials [5]. Another revealed that MIT induced a gradual, competitive P-adrenergic blocking effect against the positive chronotropic action of isoproterenol [6].…”
Section: Bradycardia Due To Mitoxantrone Exacerbated By Previous Anthmentioning
confidence: 99%